Reverse gyrase functions as a DNA Renaturase: annealing of complementary single-stranded circles and positive supercoiling of a bubble substrate. - Hsieh, T.; Plank, J.L. (Journal of Biological Chemistry, 2006)
Reverse gyrase is a hyperthermophile-specific enzyme that can positively supercoil DNA concomitant with ATP hydrolysis. However, the DNA supercoiling activity is inefficient and requires an excess amount of enzyme relative to DNA. We report here several activities that reverse gyrase can efficiently mediate with a substoichiometric amount of enzyme. In the presence of a nucleotide cofactor, reverse gyrase can readily relax negative supercoils, but not the positive ones, from a plasmid DNA substrate. Reverse gyrase can completely relax positively supercoiled DNA, provided that the DNA substrate contains a single-stranded bubble. Reverse gyrase efficiently anneals complementary single-stranded circles. A substoichiometric amount of reverse gyrase can insert positive supercoils into DNA with a single-stranded bubble, in contrast to plasmid DNA substrate. We have designed a novel method based on phage-mid DNA vectors to prepare a circular DNA substrate containing a single-stranded bubble with defined length and sequence. With these bubble DNA substrates, we demonstrated that efficient positive supercoiling by reverse gyrase requires a bubble size larger than 20 nucleotides. The activities of annealing single-stranded DNA circles and positive supercoiling of bubble substrate demonstrate that reverse gyrase can function as a DNA renaturase. These biochemical activities also suggest that reverse gyrase can have an important biological function in sensing and eliminating unpaired regions in the genome of a hyperthermophilic organism.